Characterization of black carbon-containing particles from soot particle aerosol mass spectrometer measurements on the R/V Atlantis during CalNex 2010 - Massoli, Paola; Onasch, Timothy B.; Cappa, Christopher D.; Nuamaan, Ibraheem; Hakala, Jani; Hayden, Katherine; Li, Shao-Meng; Sueper, Donna T.; Bates, Timothy S.; Quinn, Patricia K.; Jayne, John T.; Worsnop, Douglas R. (JOURNAL OF GEOPHYSICAL RESEARCH-ATMOSPHERES, 2015)
We present mass spectrometry measurements of black carbon-containing particles made on board the R/V Atlantis during the CalNex (California Research at the Nexus of Air Quality and Climate Change) 2010 study using an Aerodyne Research Inc. soot particle aerosol mass spectrometer (SP-AMS). The R/V Atlantis was deployed to characterize air masses moving offshore the California coast and to assess emissions from sources in urban ports. This work presents a first detailed analysis of the size-resolved chemical composition of refractory black carbon (rBC) and of the associated coating species (NR-PMBC). A colocated standard high-resolution aerosol mass spectrometer (HR-AMS) measured the total nonrefractory submicron aerosol (NR-PM1). Our results indicate that, on average, 35% of the measured NR-PM1 mass (87% of the primary and 28% of the secondary NR-PM1, as obtained from the mass-weighted average of the NR-PMBC species) was associated with rBC. The peak in the average size distribution of the rBC-containing particles measured by the SP-AMS in vacuum aerodynamic diameter (d(va)) varied from 100 nm to 450 nm d(va), with most of the rBC mass below 200 d(va). The NR-PMBC below 200 nm d(va) was primarily organic, whereas inorganics were generally found on larger rBC-containing particles. Positive matrix factorization analyses of both SP-AMS and HR-AMS data identified organic aerosol factors that were correlated in time but had different fragmentation patterns due to the different instruments vaporization techniques. Finally, we provide an overview of the volatility properties of NR-PMBC and report the presence of refractory oxygen species in some of the air masses encountered.